Reuleut Timu Village Youth Empowerment through Service Training for Refrigeration Equipment in the Neighborhood of Malikussaleh University - Aby, Muhammad; Putra, Reza; Asnawi, A; Muhammad, M; Islami, Nurul; Dailami, D; Rianda, Faizar (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2024)
The environment of the Reuleut Campus of Malikussaleh University has a dense area along with the increase in the number of students who inhabit the area. The number of offices and boarding houses with AC facilities is an opportunity for a property as an AC service technician and the increasing need for AC Service Technicians. The purpose of the service is to provide knowledge and skills in the maintenance and repair of Split Water Conditoner (AC) to the Youth of the Environmental Village of Malikussaleh University. The implementation of Service activities was carried out with Berkat Maju Service partners located at SP KKA Dewantara District, North Aceh Regency. The training uses theoretical, practical and internship methods. In the first method, participants are given knowledge related to theory in the form of practical support materials. Practice Methods related to air conditioner maintenance and repair starting from the introduction of work aids, installation and disassembly, service and damage detection are carried out directly by providing 1 unit of air conditioner as a practice material. Internship methods are carried out to provide participants with direct experience in the field conditions alongside partners The results of the activity show an increased level of participant knowledge about cooling equipment, based on evaluation data that indicates understanding of basic cooling equipment, equipment servicing, AC disassembly, and proper Freon detection.